Seismic and Electrical Geophysical Characterization of an Incipient Coastal Open‐System Pingo: Lagoon Pingo, Svalbard. Issue 3 (4th March 2022) - Hammock, Craig P.; Kulessa, Bernd; Hiemstra, John F.; Hodson, Andrew J.; Hubbard, Alun
Abstract: Whilst there has been a recent appreciation for the role of open‐system pingos in providing a fluid‐flow conduit through continuous permafrost that enables methane release, the formation and internal structure of these ubiquitous permafrost‐diagnostic landforms remains unclear. Here, we combine active‐source seismic measurements with electrical resistivity tomography to investigate the structural and subsurface characteristics of an incipient open‐system pingo actively emitting methane within the glacio‐isostatically uplifting fjord valley of Adventdalen, Svalbard. Wavefront inversion of seismic refractions delineate a spatially heterogeneous active layer, whilst deeper reflections identify the lithological boundaries between marine sediments and underlying shales at ∼68 m depth (p‐wave velocity of ∼1, 790 ms −1 ). Low geometric mean inverted resistivities of 40–150 Ωm highlight the dominance of saline permafrost, whilst elevated resistivities (∼2 kΩm) occur close to the groundwater spring and in heaved areas around the pingo. Based on our results, we speculate that segregation ice dominates the pingo structure, given the absence of a notable resistivity contrast characteristic of injection ice that is typically expected within early open‐system pingo formation, and provides the most plausible geomorphic agent within the local fine‐grained sedimentology. Our results thereby indicate that sediment grain size and moisture availability can provide important controls on pingo formation. This study shows that open‐system pingos in coastal, saline permafrost environments may form differently, with implications for localized permafrost structure, its permeability to underlying gas reservoirs and consequent methane release. Plain Language Summary: Considerable amounts of methane, a potent greenhouse gas, can flow through ground which is permanently below freezing (permafrost) through dome‐shaped landforms called open‐system pingos. These landforms occur in the lowlands of mountainous cold regions, from water under pressure from deep underground. However, the formation and internal structure of these landforms are unclear. We use geophysical techniques involving seismic waves and electrical resistivity to characterize the internal structure of a young pingo in Svalbard. Our seismic investigation find a seasonally thawing (active) layer with a variable thickness, and a deeper reflection at ∼68 m which we interpret as the boundary between marine sediments and bedrock. Meanwhile, relatively low electrical resistivities indicate that the ground is saline, and suggest an internal structure that is dominated by discrete layers of ice known as segregated ice, as opposed to a large body of ice which is ordinarily expected. Our results indicate that sediment grain size and moisture availability are important controls on pingo formation. This is important as there may be differences in how these pingos form, and this will impact the structure of local frozen ground and in how they allow the escape of methane stored deep beneath the permafrost. Key Points: Seismic refraction, reflection and electrical resistivity tomography are used to characterize a coastal methane‐emitting incipient pingo Low resistivities and geomorphology preclude massive ice presence, and indicate segregation ice dominates early pingo internal structure Sedimentology and moisture availability are critical controls on early pingo formation, and causes plurality within pingo structures